Standardization And Evaluation Of The Catharanthus Roseus Extract - Rehman, Nasira Saif Ur (2012)
A standardized Catharanthus roseus extract has been prepared by water and ethanol method. The widely used anticancer Vinca alkaloids, vinblastine (VBL) and vincristine (VCR) present in the extract were determined by using HPLC. Contents of VBL and VCR were determined to assess the contribution of these alkaloids towards the anticancer activity of the extract. The method was validated in accordance to the procedure mentioned in the Guidelines of USFDA and ICH. The method was found efficient and reproducible. The minimum detectable limit of VCR was 0.25 g/ml and VBL was 0.50 g/ml. An acceptable linearity was exhibited with regression coefficient (R2) of 0.9999 to 1. The first eluted alkaloid was vincristine its retention time (Rt) was 3.2 minutes followed by vindoline 3.56 minutes, vinblastine 3.89 minutes and catharanthine 4.14 minute. The content of VBL for the ethanol extracts E1, E3, E4 and E6 were 11.9μg/100mg, 9.0μg/100mg, 12.3μg/100mg and 14.4μg/100mg of the dried extract. The contents of VBL determined in water extracts W1, W3, W4, W6 were 8.2μg/100mg, 11.0μg/100mg, 10.3μg/100mg and 7.5μg/100mg. Amount of VCR present in Catharanthus roseus extracts E1, E3, E4, E6, W1, W3, W4, W6 was determined as 19.9μg, 13.2μg, 8.1μg, 26.3μg, 8.2μg, 13.1μg, 11.1μg, and 11.6 μg/100mg of the dried extract. The study of the extract on cancer cells demonstrated good cytotoxic activity. Ethanol extract E6 showed acceptable cytotoxicity against breast cancer cells T47D (IC50 12g/ml). Water extract W6 showed pronounced anticancer activity against colon cancer cell lines HCT116 (IC50 10 g/ml) and HT29 (IC50 1.98 g). Ethanol/water extract WI was also active against both colon cancer cell lines HCT116 (IC50 12.28 g) and HT29 (IC50 1.65 g). In single dose acute oral toxicity test, variables (body weight and feed intake) were carefully checked and no significant changes in these variables were initiated. There was no difference in physical state, behavior and response of the control and the treated groups. This study indicated that water and ethanol extracts were less toxic and can be administered orally.